Environmental Salmonella in Agricultural Fair Poultry Exhibits in Colorado. (15th June 2013) - Pabilonia, K. L.; Cadmus, K. J.; Lingus, T. M.; Bolte, D. S.; Russell, M. M.; Van, D. C.; Erdman, M. M.
Summary Salmonella enterica is a common zoonotic pathogen in humans. Transmission typically occurs through consumption of contaminated food products or contact with infected animals, including poultry or their environment. The objective of this study was to estimate the frequency of Salmonella contamination in the environment in poultry exhibits at agricultural fairs. Samples were collected from cages, feed, floors and tables in the exhibit and cultured for Salmonella. At least one environmental sample was positive for Salmonella in 10 of 11 fairs (91%), and Salmonella was isolated from 28 of 55 environmental samples (50.9%). Eleven different serotypes were detected. Results of this study demonstrate that environmental surfaces at agricultural fairs can be contaminated with Salmonella and could potentially serve as a route of transmission to bird owners and the general public. Poultry owners and the general public should be educated about the risks of Salmonella infection from the poultry exhibit environment. Agricultural fairs should consider instituting policies and practices to improve hygiene and mitigate the risk of zoonotic salmonellosis.